PENERAPAN MANAJEMEN ASET DENGAN MAPYOURTAG PADA PERGURUAN TINGGI - Khanna Tiara; Hendra Kusumah; Dian Mustika Putri (UNIVERSITAS RAHARJA, 2017)
In an enterprise, good asset management system is very important role to creat an enterprise management that has a high performance in terms of service. Asset management methods which applied, must be effective and efficient in its implementation. Now, asset management methodswhich applied still very conventional that is with manually writing the report, then the report is inputted into a data processing application, this make an asset management system running ineffective because it through a very long process. To improve the asset management process,then implemented a barcode system, where each barcode representing each asset to show the identity of each asset in the form of the date of beginning the operation, the type of each asset, along with the location of each asset operated. With the barcode, the asset management processat Perguruan Tinggi Raharja run effectively without having to print the form checklists and updated the data directly into a database system, so that decision-making on assets managed to effectively by using MapYourTag application. On this research, using mind-mapping and swot analysis methods. Results from this research in the form of asset management application system by scanning the barcode that has been created for each asset that are connected directly to a database that has a dashboard that shows statistics on each asset control treatment, so that monitoring become more effective, optimal and facilitate in making asset management reports. With this system, it is expected the asset management system that applied at Perguruan Tinggi Raharja can improve sustainable development in the the life cycle of an asset.